2023
DOI: 10.3390/biom13091396
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Running Improves Behavioral and Structural Abnormalities in a Mouse Model of CDKL5 Deficiency Disorder

Nicola Mottolese,
Beatrice Uguagliati,
Marianna Tassinari
et al.

Abstract: Cyclin-dependent kinase-like 5 (CDKL5) deficiency disorder (CDD) is a rare neurodevelopmental disease caused by mutations in the X-linked CDKL5 gene. CDD is characterized by a broad spectrum of clinical manifestations, including early-onset refractory epileptic seizures, intellectual disability, hypotonia, visual disturbances, and autism-like features. The Cdkl5 knockout (KO) mouse recapitulates several features of CDD, including autistic-like behavior, impaired learning and memory, and motor stereotypies. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…To establish the effect of treatment with P021 on hippocampal neurogenesis, we rst evaluated the number of BrdU-positive cells in the hippocampal dentate gyrus (DG). As previously reported [31], no difference in the number of BrdU-positive cells was found between Cdkl5 −/Y and Cdkl5 +/Y mice (Fig. 3A); treatment with P021 showed a small but non-signi cant increase on progenitor cell proliferation (Fig.…”
Section: Effect Of Juvenile Treatment With P021 On Behaviors Of Cdkl5...supporting
confidence: 84%
See 3 more Smart Citations
“…To establish the effect of treatment with P021 on hippocampal neurogenesis, we rst evaluated the number of BrdU-positive cells in the hippocampal dentate gyrus (DG). As previously reported [31], no difference in the number of BrdU-positive cells was found between Cdkl5 −/Y and Cdkl5 +/Y mice (Fig. 3A); treatment with P021 showed a small but non-signi cant increase on progenitor cell proliferation (Fig.…”
Section: Effect Of Juvenile Treatment With P021 On Behaviors Of Cdkl5...supporting
confidence: 84%
“…Recent ndings have indicated that neurotrophic factors such as BDNF can serve as potential therapeutic candidates in neurodevelopmental disorders such as Rett syndrome and CDD [30,31,56,57]. In this study, we examined the effects of a CNTF-derived peptidergic compound, P021, on neuronal maturation and survival in a human cellular model and in a mouse model of CDD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to sedentary controls, both Cdk l5 KO mice ( 262 ) and VPA-induced rats ( 204 ) after one month of wheel/treadmill running showed increased hippocampal neurogenesis, improved memory performance, and reduced anxious and impulsive behaviors. One-month voluntary wheel running not only can decrease hippocampal microglia overactivation in Cdkl5 KO mice ( 262 ), but also stimulate microglia-mediated engulfment of surplus synapses in the granule cell axons observed in MIA mice ( 229 ). On the other hand, however, high-intensity exercise may produce negative effects on ASD symptoms.…”
Section: Therapies That Positively Influence the Structure And Functi...mentioning
confidence: 99%